Given:
The function f(x) is defined as:
![f(x)=x^2\text{ - 3x - 4}](https://img.qammunity.org/2023/formulas/mathematics/college/etlfryh16lscfrxqpk2vl8x6vjq2xsrifz.png)
Required: The axis of symmetry of the equation
The first step is the define the formula
Given the general equation of a parabola to be:
![y=ax^2+bx+c](https://img.qammunity.org/2023/formulas/mathematics/high-school/g7mvpjunjwe6qob7ddy7l4f0glbtdi9gci.png)
The axis of symmetry is defined as:
![x\text{ = }-(b)/(2a)](https://img.qammunity.org/2023/formulas/mathematics/college/kci1ku3icuu6tk0pkb6mb56l2ezlwy3c19.png)
The next step is to apply the formula
a =1 , b = -3
![\begin{gathered} x\text{ = -}(-3)/(2*1) \\ =\text{ }(3)/(2) \\ =\text{ 1.5} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/8192omewj7wyatpx9lkfmcl20qrloxmqs1.png)
Hence, the axis of symmetry is x = 1.5
Answer: Option D